Hydraulic Performance Evaluation of Cooling Water Systems in Air Separation Units Using Pressure Drop - Muhammad Fadhil Nasrullah; Fahrudin; Nicky Yonkimandalan; Shofia Putri Aulia; Putty Fauthyda Zahra Hapidzha; Regina N. Lumbantoruan (Fakultas Teknik Universitas Pancasila, 2026)
Cooling water systems are crucial for maintaining the reliability of industrial processes. Excessive pressure losses in the pipeline network increase the system head requirements, resulting in higher pump power consumption and reduced hydraulic performance. This study aims to evaluate the hydraulic performance of the cooling water system through pressure drop analysis and pump operating point evaluation under actual operating conditions. Major losses were calculated using the Darcy–Weisbach equation, while minor losses were determined using the Crane loss coefficient method. The total pressure drop was converted to system head and then used to calculate hydraulic power, pump shaft power, and pump operating point. The results showed a total major loss of 243,459.40 Pa, a total minor loss of 488,497.74 Pa, and a total pressure drop of 731,957.15 Pa, which corresponds to a system head of 74.61 m. The calculated hydraulic power and pump shaft power were 14,233 kW and 21,896 kW, respectively. The operating point evaluation confirmed that excessive hydraulic resistance affected the pressure distribution in the cooling water system. The proposed pump selection meets the calculated hydraulic requirements and provides an engineering basis for improving system reliability, hydraulic efficiency, and pump performance.